Why did Paul make so little of the birth of Jesus? - Sebothoma, W. A. (Hervormde teologiese studies, 1994)
The parameters of the question in the title involve a comparative study of ‘the birth of Jesus’, its historicity or function within the synoptic tradition. The results are weighed against Pauline theology, its thrust as well as conceptual range. The pre-existent aspect of the notion of Messiah, which constitutes the condition for the possibility of the infancy narratives, is scrutinized in order to determine the validity or otherwise of the ‘report’ on ‘the birth of Jesus’.